Extensões ao HMBS para Especificação de Apresentações Hipermídia - Paulo, Fabiano Borges; Masiero, Paulo Cesar; Oliveira, Maria Cristina Ferreira de (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1996: Anais do X Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1996.24456, 1996)
Hypermedia refers to the integration of hypertext and multimedia in a single communication model. The use of models for specifying hypermedia applications (or hyperdocuments) provide a systematic approach towards development which can improve the quality of the final produts. HMBS is a model which allows the specification of hypertext navigational requirements. In this work, the scope of HMBS is expanded with the inclusion of mechanisms that enable the specification of hypermedia requirements.